Analysis of the feasibility of execution of precast ramps (Research, Society and Development, 2022)
It deals with the research on Executive feasibility of precast ramps, from the perspective of civil engineering. Prefabricated pedestrian ramps are slip-resistant and low maintenance, while prefabricated loading ramps are pre-engineered and customizable by length, width and height. objective to discuss the way of building precast ramps approaching the structure made in engineering. This study, because it is a bibliographical research, brought scholars in the area that show how important analysis of the feasibility of the execution of precast ramps is and to conclude that cast-in-place concrete is more financially viable in the short term, the pre-cast molding that needs skilled labor and heavy machinery, which would be a great disadvantage in the long run, making the work in molded-in-place economically more advantageous.